27. CURRENT STATUS OF MEDICAL EXAMINATION AND TREATMENT SERVICE QUALITY AT THE DAY TREATMENT DEPARTMENT OF CHILDREN’S HOSPITAL 2, HO CHI MINH CITY IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: (1) Evaluate the quality of medical examination and treatment services at the Day Treatment Department of Children's Hospital 2, Ho Chi Minh City in 2024; and (2) Analyze some factors affecting the quality of medical examination and treatment services.Method: Descriptive cross-sectional study from August 2023 to August 2024.Results: The overall agreement rate of pediatric patients’ relatives on the quality of medical examination and treatment services at the Day Treatment Department of Children's Hospital 2 in 2024 was 85.6% with an average score of 4.01 ± 0.583. Some factors related to the opinions of the pediatric patient’s family about the quality include gender, education, number of visits and the number of services provided.Conclusions: The study shows that in order to improve the quality of medical examination and treatment services at the Day Treatment Department, the Children's Hospital 2 needs to conduct more studies to survey the opinions of patients, thereby providing a basis for implementing effective improvement measures.
Keywords: Quality of medical examination and treatment services; KQCAH; day treatment department; Children's Hospital 2